2018
DOI: 10.1007/s00330-018-5584-y
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month prostate volume reduction after MRI-guided transurethral ultrasound ablation of the prostate

Abstract: • MRI-guided transurethral ultrasound ablation (TULSA) achieved an 88% reduction of viable prostate tissue volume at 12 months, in excellent agreement with expectation from thermal dose calculations. • Non-perfused volume on immediate post-treatment contrast-enhanced MRI represents only 64% of the acute thermal ablation volume (ATAV), and reports only 60% (53% instead of 88% achieved) of the reduction in viable prostate tissue volume at 12 months. • MR-thermometry-based predictions of 12-month prostate volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…The use of an endo-rectal coil is not a standard procedure at our center since it is expensive and sensitive to artifacts, but it was helpful in treating this large fibroid located in the recto-sigmoid region. The use of another endo-rectal device without a coil, but with a cooling system, has been previously described for MR-HIFU prostate treatment with the TULSA-PRO system [20]. However, this device is not inflatable and may therefore not provide enough pressure to move the fibroid anteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an endo-rectal coil is not a standard procedure at our center since it is expensive and sensitive to artifacts, but it was helpful in treating this large fibroid located in the recto-sigmoid region. The use of another endo-rectal device without a coil, but with a cooling system, has been previously described for MR-HIFU prostate treatment with the TULSA-PRO system [20]. However, this device is not inflatable and may therefore not provide enough pressure to move the fibroid anteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with TULSA Procedure MRI-guided TULSA of the prostate was delivered using the TULSA-PRO system (Profound Medical, Mississauga, ON, Canada) with the patient inside the bore of a 3-T MRI unit (Magnetom Trio, Siemens, Munich, Germany) as described previously [5,6]. The Urologist and Radiologist contoured the prostate from transverse MR images for treatment planning, monitored treatment delivery real time from live MRI temperature maps, and finally verified satisfactory treatment completion with gadolinium-enhanced post-treatment MR scan.…”
Section: Methodsmentioning
confidence: 99%
“…The first prospective evaluation of TULSA was a Phase I multicentre study of the safety and feasibility of near wholegland ablation in a primarily low-risk patient population [5,6]. Therein, the treatment plan was intentionally conservative, sparing a 3-mm rim of prostatic tissue from the capsule (equivalent to 10% of the prostate tissue volume remaining viable).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal micturation function returned in all cases by 6 months . Bonekamp et al performed a review in 30 patients undergoing MR‐guided US ablation of the prostate and found that immediate posttreatment contrast MR imaging underrepresented the entire thermal ablation volume compared to that seen 12 months after the procedure. Burtnyk et al found 0.9‐mm accuracy and precision at necropsy in 8 patients undergoing transurethral prostate ablation using MR thermographic guidance.…”
Section: Magnetic Resonance Versus Us Guidance For Hifumentioning
confidence: 99%